Sex-Specific Brain Transcriptional Signatures in Human MDD and Their Correlates in Mouse Models of Depression - Touchant, Maureen; Labonté, Benoit (Frontiers in Behavioral Neuroscience, 2022)
Major depressive disorder (MDD) is amongst the most devastating psychiatric conditions affecting several million of people worldwide every year. Despite the importance of this disease and its impact on modern societies, still very little is known on the etiological mechanisms. Treatment strategies have stagnated over the last decades and very little progress has been made to improve the efficiency of current therapeutic approaches. In order to better understand the disease, it is necessary for researchers to use appropriate animal models that reproduce specific aspects of the complex clinical manifestations at the behavioral and molecular levels. Here, we review the current literature describing the use of mouse models to reproduce specific aspects of MDD and anxiety in males and females. We first describe some of the most commonly used mouse models and their capacity to display unique but also shared features relevant to MDD. We then transition toward an integral description, combined with genome wide transcriptional strategies. The use of these models reveals crucial insights into the molecular programs underlying the expression of stress susceptibility and resilience in a sex-specific fashion. These studies performed on human and mouse tissues establish correlates into the mechanisms mediating the impact of stress and the extent by which different mouse models of chronic stress recapitulate the molecular changes observed in depressed humans. The focus of this review is specifically to highlight the sex differences revealed from different stress paradigms and transcriptional analyses both in humans and animal models.